The role of a strong organization in crisis management - an analytical study of the opinions of managers in the Cihan Group of Companies in the city of Erbil - Khaled Hamad Amin Mirkan; Dina Aziz Mohammed Ahmed Alsaji (Iraqi Journal for Administrative Sciences, 2024)
The study aims to diagnose and identify the characteristics of anti-fragile organizations, and the mechanisms required for it and availability in the surveyed companies and determine their levels, and the extent of the contribution of these characteristics together to support and strengthen the dimensions of the crisis management in those companies?, and the results can be reached in the framework of the development of those characteristics and dimensions?. To answer these questions, Cihan group companies in Erbil were selected, as a field of study, and a source for the data collected by questionnaire distributed to eight companies belonging to Cihan group, the study sample was chosen of managers only totaling (50), the study adopted to achieve its goals and come up with answers with at the sides of the theoretical and practical to the descriptive analytical approach. Relations and influences have been tested between characteristics of the anti-fragile organization and the dimensions of Crisis management using some statistical methods by SPSS.v.23 program , and in the light of the results has been reached among the conclusions referred to the active role of those characteristics adopted by the study in enhancing of the dimensions of the crisis management in the surveyed group companies . On the basis of this was to provide a set of proposals , most notably the need to pay more attention to some of the characteristics and dimensions that have been studied in order to develop and improve the surveyed companies. Key words: Anti-fragile Organization, Anti-fragility, Crisis Management.